Implementation of Al-Islam Kemuhammadiyahan Character Education through the Merdeka Curriculum in Class VI of Muhammadiyah 1 Elementary School, Sorong City - Tahang, Tarmizi -; Misriandi; Tang, Ambo (Jurnal Kependidikan Media, 2025)
Forming the character of students from an early age is an important foundation in creating a generation with dignity and value. This research aims to describe the implementation of character education based on Islamic and Muhammadiyah values through the Merdeka Curriculum approach at Muhammadiyah Elementary Schools 1 and 2, Sorong City. The research uses a descriptive qualitative method with a literature study and field observation approach. The results show that the integration of character values through ISMUBA subjects and extracurricular activities such as Duha Prayer, Tahfidz Qur'an, and Hizbul Wathan Scouting has a positive impact on changes in student behavior, such as increasing discipline, responsibility, and awareness of worship. Supporting factors in implementing character education include the availability of facilities, teacher involvement, and the flexibility of the Independent Curriculum. However, obstacles such as limited resources, teachers' understanding of the curriculum, and the negative influence of the digital environment are still challenges that need to be overcome. Overall, character education integrated with Islamic values has proven to be effective in shaping students' positive behavior, as long as it is supported by synergy between school, family and community.